Triggering bat detectors: automatic vs. manual mode - Matos, Milena (2018)
Ultrasound detectors have revolutionized the study of bats, as they allow for cost-effective gathering of large amounts of data on bat activity. The identification of bat species through the analysis of echolocation calls is possible, as long as the researcher is well aware of the features and limitations of the detector and methods used. In bat studies, field logistics frequently leads to the need of leaving the ultrasound detector in the study area for a given number of nights, set to an automatic triggering mode. Nonetheless, the reliability of this option, in comparison with the manual mode, is still uncertain, even for commonly used bat detector models. In this study, we assessed the efficacy of a popular time-expansion bat detector model set to the automatic trigger mode, when compared with the manual mode. We sampled bat activity in five different habitats for 23 nights with two bat detectors operating simultaneously, side by side, one set to manual mode and the other set to automatic mode. Our results showed significant differences in detected species richness, species diversity, and bat activity between the manual and the automatic modes. We present practical information and clarify the adequacy of using the analyzed bat detector in automatic conditions.